Effect of light and nitrogen concentration and phosphorus on growth and protein component of Oscillatoria angustissima algae - Balqis yahya Alsoufi; Mohammed Basheer Ismael; Yousef Jabar Alshahery (College of Education for Pure Sciences, 2009)
ABSTRACT An is isolate of Oscillatoria angustissima was obtained from local environment at Mosul city. The results showed that the growth was high and achieved (0.399) as an optical density after fifteen days of incubation in a continuous light's period. While the growth reach upto (0.309) as an optical density when the culture exposed to 12 hour light and 12 hour dark, but did not achieve any growth when it used continuo's dark period. For all used photoperiods, the final pH was significantly higher than the primary pH. The maximum growth for algal (0.37) as an optical density when the concentration of nitrogen in culture medium was (0.09%) while the protein content was (309) mg/L when the concentration of nitrogen in culture medium was (0.15%). The results also showed that the maximum growth for algal (0.33) as an optical density was achieved when the concentration of phosphor in culture medium was (0.13%) and protein content was (288) mg/L. The final pH was significantly higher than the primary pH for all the used concentration nitrogen and phosphor.